Age-related changes in crystalline lens tilt and decentration: swept-source OCT study. Issue 10 (October 2021) - Li, Zhangliang; Zhu, Zehui; Li, Xiuyuan; Meng, Ziqi; Qu, Wenyong; Zhao, Yune
Abstract : In this study, the crystalline lens tilt and decentration were measured using swept-source coherence tomography. The crystalline lens position correlated with ocular parameters and may change over time. Abstract : Purpose: To investigate the age-related tilt and decentration of crystalline lenses using a swept-source optical coherence tomography biometer (SS-OCT) (CASIA2, Tomey Corp.). Setting: Eye Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, China. Design: Cross-sectional study. Methods: The direction and magnitude of the crystalline lens were evaluated in 230 participants with ages ranging from 7 to 90 years using SS-OCT. The participants were divided into 4 age groups, and the differences among the groups were analyzed. Multiple linear regression was used to investigate the main factors influencing crystalline lens tilt and decentration. Results: The natural crystalline lens tilted toward the inferotemporal direction with a mean magnitude of 4.3 ± 1.5 degrees (range 0.7 to 8.95 degrees). The mean decentration toward the superotemporal direction was 0.17 ± 0.12 mm (range 0.03 to 1.15 mm). There was mirror symmetry between the right and left eyes. There were statistically significant differences in the crystalline lens tilt and decentration among the age groups. Multiple linear regression showed that changes in crystalline lens tilt depended on angle α ( P < .01) and anterior chamber depth (ACD; P = .008), whereas crystalline lens decentration depended on angle κ ( P = .003), age ( P < .01), and angle α ( P = .002). Conclusions: Although there was a statistically significant difference in crystalline lens tilt and decentration among age groups, the variation in the crystalline lens position was partially affected by age. The crystalline lens tilt was greater in eyes with wider angle α and shallower ACD, whereas crystalline lens decentration was greater in younger eyes with wider angles κ and α.